2000
DOI: 10.1161/01.cir.102.6.605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plasma Homocysteine Concentration on Early and Late Events in Patients With Acute Coronary Syndromes

Abstract: Elevated total homocysteine levels on admission strongly predict late cardiac events in acute coronary syndromes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
3
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(74 citation statements)
references
References 32 publications
3
64
3
4
Order By: Relevance
“…3,4 Our data describing a direct positive relation between homocysteine and subsequent vascular events within the AFCAPSA/Tex-CAPS cohort are consistent with most but not all prior studies of homocysteine and vascular risk. [5][6][7][8][9][10][11]17 Particular strengths of the present analysis that we believe increase its validity and generalizability include our large sample size, the use of a validated commercial assay for homocysteine assessment, and clear end point definitions and complete cohort ascertainment.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…3,4 Our data describing a direct positive relation between homocysteine and subsequent vascular events within the AFCAPSA/Tex-CAPS cohort are consistent with most but not all prior studies of homocysteine and vascular risk. [5][6][7][8][9][10][11]17 Particular strengths of the present analysis that we believe increase its validity and generalizability include our large sample size, the use of a validated commercial assay for homocysteine assessment, and clear end point definitions and complete cohort ascertainment.…”
Section: Discussionmentioning
confidence: 98%
“…[9][10][11] Partly on the basis of these observations, homocysteine screening also has been advocated as a method to improve detection of high-risk patients. However, no data are available addressing whether homocysteine evaluation might, like CRP, provide a method to better target statin therapy among those with low-to-normal LDL cholesterol levels.…”
mentioning
confidence: 99%
“…The profession does not seem to have caught up with the fact that there are beneficial lipoproteins of high density (HDL). The factors in non-diabetic patients that subsequent events did correlate with were: infarct size (as assessed by troponin [15], previous ACS, insulin resistance [16], plasma homocysteine rose above normal [17] and raised lipoprotein(a) [18]. Of particular interest was the link between raised homocysteins and pro-thrombosis [19].…”
Section: Causative Factors In Patientsmentioning
confidence: 99%
“…It was suggested that lowering Hcy levels by 3μmol/L (by increasing folic acid intake) would reduce the risk of CHD by 16%, deep vein thrombosis by 25% and stroke by 24% [95]. Finally, in some studies raised Hcy levels emerged as a strong predictor of adverse clinical outcomes in patients with acute coronary syndromes (ACS) [101][102][103].…”
Section: Hcy and Cvdmentioning
confidence: 99%